A case study in knowledge acquisition for logistic cargo distribution data mining framework - Puteri Nohuddin,; Zuraini Zainol,; Lee, Angela Siew Hoong *; Imran Nordin,; Zaharin Yusoff, * (Institute of Advanced Science Extension (IASE), 2018)
Knowledge acquisition is one of important aspect of Knowledge Discovery in Databases to ensure the correct and interesting knowledge is extracted and represented to the stakeholders and decision makers. The process can undertake using several techniques as such in this study, it is using data mining to extract the knowledge patterns and representing the knowledge described using ontology based representation. In this paper, a data set of Logistic Cargo Distribution is selected for the experiment. The dataset describes the shipment of logistic items for the Malaysian Army.